Structural insights into the regulatory mechanism of the response regulator RocR from Pseudomonas aeruginosa in cyclic di-GMP signaling - Rao, Feng. (2013)
The nucleotide messenger cyclic di-GMP (c-di-GMP) plays a central role in the regulation of motility, virulence, and biofilm formation in many pathogenic bacteria. EAL domain-containing phosphodiesterases are the major signaling proteins responsible for the degradation of c-di-GMP and maintenance of its cellular level. We determined the crystal structure of a single mutant (R286W) of the response regulator RocR from Pseudomonas aeruginosa to show that RocR exhibits a highly unusual tetrameric structure arranged around a single dyad, with the four subunits adopting two distinctly different conformations. Subunits A and B adopt a conformation with the REC domain located above the c-di-GMP binding pocket, whereas subunits C and D adopt an open conformation with the REC domain swung to the side of the EAL domain. Remarkably, the access to the substrate-binding pockets of the EAL domains of the open subunits C and D are blocked in trans by the REC domains of subunits A and B, indicating that only two of the four active sites are engaged in the degradation of c-di-GMP. In conjunction with biochemical and biophysical data, we propose that the structural changes within the REC domains triggered by the phosphorylation are transmitted to the EAL domain active sites through a pathway that traverses the dimerization interfaces composed of a conserved regulatory loop and the neighboring motifs. This exquisite mechanism reinforces the crucial role of the regulatory loop and suggests that similar regulatory mechanisms may be operational in many EAL domain proteins, considering the preservation of the dimerization interface and the spatial arrangement of the regulatory domains.